Intention to purchase behavior on social e-commerce website across cultures (case study: Iranian online purchaser) - Rezaeian, Ali; Shokouhyar, Sajjad; Yousefi, Shahabedin (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
With the increasing popularity of social media, millions of users use social media services in the space such as Facebook, Twitter, MySpace, etc. Following that many organizations see this phenomenon as an opportunity to create new business and know this is known as social commerce. This phenomenon is not only due to the growth of social media, but is also because of users' participation in the fate of the marketing and sale of products. So, e-commerce has undergone a revolution, which is affected by the adoption of web 2 functionalities to increase customer participation and achieve greater economic value. Therefore, studying the behavior of buyers in the social commerce platforms can create more value for owners of e-commerce in the context of social commerce. For this reason, attempts were made to obtain more accurate findings regarding the behavior of e-commerce purchasers in social networks by taking into account the moderating influence of culture on it (Iranian online purchasers).This is an applied study. It also considered a descriptive cross-sectional study with regards to the way data are collected. The analysis of data collected from 184 active professionals in the IT industry and users of social networks indicates the moderating effect of culture and the mediating role of trust in a social network community in terms of social identity, trust transference (Familiarity), social influence (intimacy and friendship), cognitive style and the intention to purchase in the social business environment. Moreover, these findings also show that trust transference affects intention to purchase in social networks considering the aspects of familiarity, social identity and cognitive style. But the direct effect of social influence (feel close to) on the purchase intention has been rejected.